2020
DOI: 10.3390/jcm9082379
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Clinical Outcome in a Matched Case-Control Cohort of Polytrauma Patients Following an Osteosynthetic Flail Chest Stabilization

Abstract: Background: In polytrauma (PT) patients, osseous thoracic injuries are commonly observed. One of the most severe injuries is the flail chest where the rib cage is broken in such a way that leads to a partial functional detachment of the thoracic wall. Especially in PT patients, the integrity of the respiratory system and especially, of the respiratory muscles is essential to prevent respiratory failure. Besides conservative treatment options, flail chest injuries may be surgically stabilized. However, this tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Aufgrund inhomogener chirurgischer Strategien und kaum vergleichbarer Kollektive ist die bisherige Datenlage hinsichtlich der Indikation zur frühzeitigen Osteosynthese von Segmentverletzungen der Rippen inkonklusiv. Auch eine retrospektive Studie aus unserem Zentrum zeigte ein annähernd gleiches Outcome zwischen operativ und konservativ Behandelten 5 . Es muss jedoch angemerkt werden, dass die Indikation zur Osteosynthese in unserem Zentrum bislang als letzte Therapieoption gestellt wird.…”
Section: Abstract Marcel Niemannunclassified
“…Aufgrund inhomogener chirurgischer Strategien und kaum vergleichbarer Kollektive ist die bisherige Datenlage hinsichtlich der Indikation zur frühzeitigen Osteosynthese von Segmentverletzungen der Rippen inkonklusiv. Auch eine retrospektive Studie aus unserem Zentrum zeigte ein annähernd gleiches Outcome zwischen operativ und konservativ Behandelten 5 . Es muss jedoch angemerkt werden, dass die Indikation zur Osteosynthese in unserem Zentrum bislang als letzte Therapieoption gestellt wird.…”
Section: Abstract Marcel Niemannunclassified
“…In their retrospective study, Niemann et al did not find differences in clinical parameters (e.g., the duration of mechanical ventilation, analgesia requirements, pneumonia incidence) between conservatively and operatively treated patients. However, a prolongation of both the length of intensive care unit (ICU) stay and hospital treatment duration was observed in operatively treated patients [5]. In a further study with a retrospective design, Eckhardt et al confirmed the relevance of chest trauma in the posttraumatic course (longer ventilation time, prolonged ICU stay, increased mortality) Interestingly, being overweight resulted in an independent mortality reduction in patients with severe chest trauma [6].…”
mentioning
confidence: 99%